Insights into D4h@metal-symmetry single-molecule magnetism: the case of a dysprosium-bis(boryloxide) complex. Issue 6 (21st December 2020) - Thomas-Hargreaves, Lewis R.; Hunger, David; Kern, Michal; Wooles, Ashley J.; van Slageren, Joris; Chilton, Nicholas F.; Liddle, Stephen T.
Abstract : We report a D 4h @Dy single-molecule magnet (SMM) with a U eff energy barrier of 1565 K, one of the highest energy barriers for any 6-coordinate lanthanide SMM. Abstract : We report the synthesis of the lanthanide-(bis)boryloxide complex [DyOB(NArCH)2 2 (THF)4 ][BPh4 ] (2Dy, Ar = 2, 6-Pr i 2 C6 H3 ), with idealised D 4h @Dy(iii ) point-group symmetry. Complex 2Dy exhibits single-molecule magnetism (SMM), with one of the highest energy barriers ( U eff = 1565(298) K) of any six-coordinate lanthanide-SMM. Complex 2Dy validates electrostatic model predictions, informing the future design of lanthanide-SMMs.